Effect of combined genetic polymorphisms on lung cancer risk in northern Thai women - Klinchid J. (2014)
Lung cancer is a major cause of cancer-related death in developed countries, and its incidence in developing countries is increasing. In Thailand, cancer incidences differ greatly from region to region, and lung cancer is the most common cancer in the northern Thai population. The polymorphic frequency of 10 genetic susceptibility genes and their association with lung cancer were examined in a northern Thai population: CYP1A1 (MspI), CYP1A1 (Ile462Val), CYP2E1 (PstI), CYP2E1 (DraI), GSTM1, GSTT1, MPO (AciI), OGG1 (Ser326Cys), TP53 (Arg72Pro), and MMP1(AluI). The 173 subjects were 91 lung cancer patients and 82 healthy volunteers. Although no significant association between any single genetic variant and lung cancer risk was observed, when genetic variants were analyzed in combination, a significant effect on lung cancer risk was found for the variant allele in a combination of five genes involved in oxidative stress and inflammatory response: GSTM1 (null), MPO (-463A), OGG1 (326Cys), TP53 (72Pro) (alias p53), MMP1 (2G). With a reference group of individuals carrying at least two wild-type genotypes of these five genes, it was found that an individual carrying three or more variant genotypes is at significantly higher risk of developing lung cancer with the increasing of odds ratios (OR) in concurrence with the number of variant genes. The OR was 2.41 (95% CI = 0.76-7.64), 3.90 (95% CI = 1.23-12.34), and 5.20 (95% CI = 1.31-20.54) for individuals carrying three, four, and five variants, respectively. After stratifying by sex, the OR was higher for women: OR 4.05 (95% CI = 0.44-36.94), 9.00 (95% CI = 0.95-84.89) and 18.00 (95% CI = 1.49-216.62) for three, four, and five variant genotypes, respectively. This augmented effect on lung cancer risk of variant genes involved in oxidative stress and inflammatory response in women with a low prevalence of smoking indicates their modifying effect on other risk factors, such as environmental cigarette smoke, air pollution, radon radiation, or infection of the airway. Confirmation would require further investigations with larger sample sizes. © 2009 Elsevier Inc. All rights reserved.